Literature Review: The Application of TPS Cooperative Learning Model In Improving Student Learning Outcomes - Wiwit, Wiwit Mustika; Gultom, Renny Bunga Evelyna; Iswara, Bintang Dwi; Mardiyanti, Lely; Siburian, Jodion; Sadikin, Ali (Perspektif Ilmu Pendidikan, 2024)
Cooperative learning can be defined as a method in which students work together in small groups to support each other's learning, with the goal of understanding class objectives and engaging in learning activities. An instructional approach that utilizes this new framework is known as Think Pair Share (TPS), a pedagogical model consisting of several learning stages that can increase student engagement and interaction. The Think Pair Share (TPS) cooperative learning model is a structured approach to group learning where students exchange ideas to improve their cognitive abilities, articulate their viewpoints, and foster collaboration among peers. The purpose of this study is to investigate the effectiveness of implementing the TPS (Think Pair Share) cooperative learning model to improve student learning outcomes. This study used a methodology by conducting a literature review. The methodology used in this literature review is based on a qualitative approach and uses data collection techniques from the literature review. Based on the results of the study, it can be concluded that the application of the TPS (Think Pair Share) type cooperative learning model can improve students' cognitive learning outcomes. The TPS Learning Model is suitable for MIPA learning because it effectively meets students' learning needs through its implementation